Greener refrigerants - Hui, Harrison Jun Jie (2017)
Singapore’s average temperature was 28.4°C for 2016. This is 13.5°C higher than the global annual mean temperature. As a result, up to 50% of the total power consumption of a household is used for air-conditioning and refrigeration. Governmental regulations and international treaties are looking to reduce fluorinated gases emissions and eventually phase them out. R134a is one of the most widely used refrigerant and therefore alternatives to current refrigerants must be identified and analysed. As Singapore is land scarce, high rise buildings are used in order to maximise space efficiency, giving rise to the stack effect, whereby the buoyancy of hot air from another condensing unit affects another. Although many studies and experiments were carried out to improve the efficiency of the refrigeration cycles, most do not consider warm climates along with other localized factors like the stack effect. This study analyses the first and second law performance of seven refrigerants, R32, R1234yf, R134a, R1234ze(E), R404a, R401a and R744 at a evaporator temperature of 0°C and -32°C with varying condenser temperature of between 54.4°C and 70.0°C. The refrigerants are also put through a modified version of the vapour compression cycle with/without superheating and or subcooling and first law analysis is performed on the system. The calculations was performed with a code written in FORTRAN coupled to the refrigerant database from the National Institute of Standards and Technology’s REFPROP. It enables the quick switching between refrigerants and can be updated with new refrigerant properties as they become available through REFPROP updates. The Coefficient of Performance (COP) drops drastically by 31.5-60.3% when the condenser’s temperature increases from 54.4°C to 70°C at the evaporator temperature of 0°C. When the evaporator temperature is reduced to -32°C, the COP reduces by 43-66% as compared to when the evaporator’s temperature is 0°C. The refrigerants that performed the worst are R744 and R404a. This is due to the R744 operating in transcritical cycle and R404a approached its critical temperature of 72.12°C at the higher condenser temperature, resulting in the greatest losses. The use of an internal heat exchanger improves the performance of the system by 0.7-6.7% with the sole exception of R32 which decreases by 1.3%. This is due to the compression work increasing faster than the cooling capacity increase due to an increased specific volume at the compressor inlet.